A special issue on housing affordability: An introduction - Ka Yui Leung; Kwok Ping Tsang (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This short note introduces a forthcoming special issue on housing affordability. It tries to relate to the recent literature as well.
Keywords: E30; H20; R30; 330; housing affordability; demand and supply; policy implications; structural model